2021
DOI: 10.17826/cumj.915323
|View full text |Cite
|
Sign up to set email alerts
|

Farklı maloklüzyon gruplarında ortodontik tedavinin mandibular kondil kemik kalitesine etkisi

Abstract: The aim of this study was to investigate the effects of orthodontic treatment on the mandibular condyle head bone formation according to different orthodontic malocclusion groups. Materials and Methods: In the study, forty-eight patients were examined. Individuals included in the study were grouped according to malocclusion groups. Our study was carried out retrospectively. The quality of mandibular condyle bone in panoramic images of patients before and after orthodontic treatment were compared retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Studies have also reported changes in sagittal and vertical angles after orthodontic treatment of CMLIM (10). In addition, differences in FD values in the alveolar bone of different skeletal malocclusions have been reported (47,48). Therefore, our study was standardized by adding patients with normal skeletal angles in order to eliminate the potential altering effect of different skeletal components on the FDs of the trabecular alveolar structure.…”
Section: Author Contributionsmentioning
confidence: 99%
“…Studies have also reported changes in sagittal and vertical angles after orthodontic treatment of CMLIM (10). In addition, differences in FD values in the alveolar bone of different skeletal malocclusions have been reported (47,48). Therefore, our study was standardized by adding patients with normal skeletal angles in order to eliminate the potential altering effect of different skeletal components on the FDs of the trabecular alveolar structure.…”
Section: Author Contributionsmentioning
confidence: 99%